A consequence of mass incarceration: county-level association between jail incarceration rates and poor mental health days - Ashley Hickson; Ritika Purbey; Lorraine Dean; Joseph J. Gallo; Roland J. Thorpe; Keshia Pollack Porter; Aruna Chandran (Health & Justice, 2022)
Abstract Introduction Mass incarceration has mental health consequences on those directly affected; some studies have also shown spillover effects on the physical health of the surrounding population. There is a dearth of research on the spillover mental health consequences of mass incarceration. This study aimed to quantify a consequence of mass incarceration which may adversely affect the population’s health and widen health disparities. Methods Using data from the Vera Institute’s Incarceration Trends 2.2 and the Robert Wood Johnson County Health Rankings, the association between county-level (n = 2823) counts of jail incarceration and reported number of poor mental health days within the past 30 days in the United States in 2018 was examined. To conduct the analysis, a negative binomial regression model was fit, adjusting for State and key demographic covariates. Results A change in jail incarceration rate from the first to the second and third tertiles was associated with 10.14% and 14.52% increases, respectively. For every 1% increase in the rate of mass incarceration, there was a statistically significant 15% increase in the average number of reported poor mental health days over the past 30 days. Discussion Mass incarceration is a threat to mental health as well as the well-being of the surrounding population. This can be attributed to the spillover effects that extend beyond those who are directly affected by mass incarceration. Interventions to reduce jail incarceration as well as address the mental health needs of those living in high-incarceration rate areas should be prioritized in order to reduce health inequities and augment health outcomes for all residents of the United States.